2022
DOI: 10.1016/j.jsxm.2022.03.354
|View full text |Cite
|
Sign up to set email alerts
|

078 Female Sexual Medicine: What Are Students Learning in Undergraduate Medical Education?

Abstract: Introduction In the United States, medical education on sexual medicine varies throughout the country and between institutions. With limited standardization, medical students and subsequent trainees have little to no training in how to approach a patient with concerns surrounding their sexual health. In 2018, half of the medical institutions in the United States required formal instruction in sexual medicine. Of those institutions that do include didactic material on sexual medicine, most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Four out of seven discussed clitoral anatomy, 6/7 mentioned the glans, 6/7 mentioned the corpora cavernosa, 6/7 mentioned the crus, 6/7 mentioned the bulb and 5/7 detailed the clitoral neurovasculature. 14 They found that there needs to be a restructuring of curriculum as it relates to female sexual medicine in undergraduate medical education. It is evident with the lack of information among the medical students in this study that our curriculum must also be examined to ensure that all parts of female anatomy are being taught to these doctors of the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four out of seven discussed clitoral anatomy, 6/7 mentioned the glans, 6/7 mentioned the corpora cavernosa, 6/7 mentioned the crus, 6/7 mentioned the bulb and 5/7 detailed the clitoral neurovasculature. 14 They found that there needs to be a restructuring of curriculum as it relates to female sexual medicine in undergraduate medical education. It is evident with the lack of information among the medical students in this study that our curriculum must also be examined to ensure that all parts of female anatomy are being taught to these doctors of the future.…”
Section: Resultsmentioning
confidence: 99%
“…'s paper in 2022, which examined preclinical curricula at seven medical schools in Chicago, Illinois. Four out of seven discussed clitoral anatomy, 6/7 mentioned the glans, 6/7 mentioned the corpora cavernosa, 6/7 mentioned the crus, 6/7 mentioned the bulb and 5/7 detailed the clitoral neurovasculature 14 . They found that there needs to be a restructuring of curriculum as it relates to female sexual medicine in undergraduate medical education.…”
Section: Discussionmentioning
confidence: 99%